Una propuesta de modelamiento para los Sistemas de Recompensa - de-los-Cobos-Silva, Sergio (2005)
One of the most important subjects of interest, in nearly any human activity, is the perception of salary. It could even be said that the decision of following a career depends deeply on the perspective that the individual may have about the future income. In this work we propose a general model for its computation. We define an employee’s reward system as a function that depends on monetary and non monetary parameters; hence, the reward system can be stated as a multiobjective system to be optimized. In the article we present a rationale of the proposed reward system, as a general model of solution, and we present come examples.